UPAYA PENINGKATAN PEMAHAMAN PENCEGAHAN INFEKSI : PADA GURU DAN WALI MURID SD MUHAMMADIYAH 3 KOTA TANGERANG - Pudyastuti, Erlina; Permata Sari, Shinta Dewi; Ardhya Yahya, Teuku Jilan; Tasbita, Kayla Taza (Universitas Negeri Surabaya, 2025)
Drastic climate change and poor air quality in several large cities contribute to the incidence of infectious diseases, especially ARIs. Preventing infection can be done to break the chain of spread of ARI, especially in children. Parents and teachers play a vital role in preventing childhood ARI. Therefore, it is necessary to increase the knowledge of infection prevention among parents and teachers. This community service activity was conducted by educating teachers and parents of students at SD Muhammadiyah 3 and SMK Muhammadiyah on infection prevention. The knowledge of the participants was evaluated by pre-test and post-test. The average score from pre-test to post-test showed an increase of 28%. Therefore, it can be concluded that there is an increase in knowledge after the training so that teachers and parents can play an active role in preventing and breaking the chain of transmission of infectious diseases in the school environment. Keywords: acute respiratory infection, education, infectious disease, air quality